LINGUO-CULTURAL ANALYSIS OF PHRASEOLOGICAL UNITS WITH COLOR COMPONENTS IN ENGLISH AND UZBEK (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
: This study explores the linguistic and cultural aspects of phraseological units (PUs) with color components in English and Uzbek languages. The analysis focuses on identifying similarities and differences in the usage and cultural connotations of these PUs. The research employs a comparative and descriptive approach, analyzing a corpus of PUs from both languages. The findings suggest that while some PUs with color components are similar in both languages, others exhibit distinct cultural and linguistic characteristics. The study contributes to a better understanding of crosscultural communication and translation between English and Uzb